The behaviors of bubble migration and pressure build-up during a dynamic shut-in procedure in deep-water drilling - Miao, Dianyuan; Hu, Junjie; Zhang, Jianbo; Wang, JinTang; Sun, Xiaohui (Frontiers in Physics, 2022)
A dynamic shut-in procedure is commonly adopted after a kick incident in order to build up the wellbore pressure, obtain reservoir information, and thereby handle the gas kick. In deep-water scenarios, the hydrate growth behaviors have a significant effect on gas migration and interphase mass transfer, which has not been quantitatively analyzed during the well shut-in process. In this study, a comprehensive mechanistic model of wellbore dynamics is developed considering gas migration and phase transitions. The simulation results show that the wellbore pressure field can be built up in different trends during different well shut-in periods, governed by gas seepage from the reservoir and gas migration along the wellbore, respectively. Masking the migration of free gas, the phase transition phenomena have a significant influence on the wellbore dynamics and bottomhole pressure. This work adds further insights into quantitatively characterizing the hydrate growth behaviors and interphase mass transfer rules of gas bubbles during a dynamic well shut-in procedure.